Aswara As An Institution For Continuity In Culture And Heritage - Che Lah, Salasiah; Esa, Norizan (Universiti Sains Malaysia, 2016)
Culture is an expression of the ways of living developed by a community and passed on from generation to generation, including customs, practices, places, objects, artistic expressions and values. Heritage is the full range of our inherited traditions, monuments, objects, and culture. Knowledge in the disciplines of culture and heritage receives less attention by the present generation especially the youth. Therefore, various efforts have been taken to attract the youth to participate in these disciplines. ASWARA Malaysia (Akademi Seni Budaya dan Warisan Kebangsaan) or National Academy of Arts, Culture and Heritage founded in 1994 has initiated moves to involve the younger generation in culture and heritage. ASWARA also is a higher institution which provides teaching and learning, research and staff publications as well as professional advice in culture and heritage. ASWARA also has staffs who are authentic practitioners. This institution merges the traditional and modern elements in disseminating knowledge as reported by the respondents who study gamelan music that includes modern and traditional musical instruments such as guitar and bass. This can attract the youth to participate in culture and heritage. It can be concluded that ASWARA is an institution that plays a role in the continuity of our own culture and heritage so that it will not become extinct.